2023
DOI: 10.47861/jkpu-nalanda.v1i3.211
|View full text |Cite
|
Sign up to set email alerts
|

Keragaman Industrialisasi Pada Kebijakan Pemerintah

Abstract: Government policies play an important role in world industry. Industrial policy is about wise government decisions in its efforts to change sentiment between industry and other economic sectors in a meaningful way, related to the sector's contribution to the economy, response rate, and income per capita. This research is part of a descriptive qualitative research on the diversity of industrialization in Indonesian government policies using various sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…West Science Interdisciplinary Studies  industrialization policies that aim to balance economic development with other sectors and increase income per capita [15]. Additionally, empirical investigations have shown that Indonesia can reduce CO2 emissions through economic growth, renewable energy use, technical advancement, and an increase in forest cover, highlighting the importance of policies for achieving environmental sustainability [16].…”
Section: Government Policies Play a Crucial Role In Shaping The Indus...mentioning
confidence: 99%
“…West Science Interdisciplinary Studies  industrialization policies that aim to balance economic development with other sectors and increase income per capita [15]. Additionally, empirical investigations have shown that Indonesia can reduce CO2 emissions through economic growth, renewable energy use, technical advancement, and an increase in forest cover, highlighting the importance of policies for achieving environmental sustainability [16].…”
Section: Government Policies Play a Crucial Role In Shaping The Indus...mentioning
confidence: 99%